IMPLEMENTASI ZIKIR SEBAGAI UPAYA MEREDUKSI CEMAS MELALUI PENDEKATAN COGNITIVE BEHAVIORAL THERAPY (CBT) - Rauhul Khotimah; Nurjannah Nurjannah (Prodi Bimbingan dan Konseling Islam Fakultas Dawah dan Komunikasi UIN Ar-Raniry, 2024)
This study aims to explain and analyze the implementation of dhikr as an effort to reduce anxiety through the Cognitive Behavioral Therapy (CBT) approach. Zikr, as a spiritual practice in the Islamic religion, has the potential to influence the thoughts, emotions and behavior of individuals. The CBT approach, which focuses on the relationship between thoughts, emotions and behavior, can be used to understand and harness the potential of dhikr in overcoming anxiety. This study involved a literature review to gather information and in-depth understanding of dhikr, CBT, and the relationship between the two in reducing anxiety. The results of this study indicate that Dhikr also helps change unhealthy thought patterns or cognitive distortions that cause anxiety, as well as provides a sense of calm and inner peace. The integration between dhikr and CBT provides a holistic approach in reducing anxiety by diverting attention, restructuring thought patterns, and creating a feeling of peace.